The promotion of miaenergism as a challenge to identity of non-Chalcedonian christianity - Kashchuk, Oleksandr (Vox Patrum, 2018)
The article discusses the question of interrelation between the promotion of Miaenergism and its influence on the sense of religious identity of non-Chalcedonian Christians. The purpose of the article if to point that the promotion of Miaenergism was perceived by Miaphysites as an challenge for their religious identity formed in the period after the Council of Chalcedon (451) on the basis of refutation of Chalcedon, absolute loyalty to the teachings of their Patriarchs, especially to Christological notions of Cyril of Alexandria. The promotion of Miaenergism became the stimulus that caused the crystallization of a sense of religious identity of the Miaphysites. The promotion of Miaenergism strongly influenced a sense of the Miaphysite political identity, opposite to Byzantine government.